Emigration and Alcohol Consumption among Migrant Household Members Staying Behind: Evidence from Kyrgyzstan - Sara Paulone; Artjoms Ivlevs (Institute of Labor Economics (IZA), 2019)
Despite the growth of alcohol consumption and international migration in many developing countries, the links between the two remain underexplored. We study the relationship between emigration of household members, receiving remittances (migrant monetary transfers), and alcohol consumption of migrant household members staying behind in Kyrgyzstan, a poor post-socialist country that has recently witnessed both large-scale emigration and a rise in alcohol-related health problems. Using a large longitudinal survey, we find that, among the ethnic majority (Kyrgyz), an increase in migrant remittances is associated with a higher likelihood and frequency of consuming alcohol, as well as an increase in the consumption of beer. Among ethnic Russians, the emigration of family members who do not send remittances back home is associated with an increased likelihood and frequency of alcohol consumption. We discuss possible mechanisms through which emigration and remittances may affect the alcohol consumption of those staying behind, including the relaxation of budget constraints and psychological distress. Overall, our findings suggest that the emigration of household members contribute to a greater alcohol consumption among those staying behind, and highlight the role of remittances and cultural background in understanding the nuances in this relationship.
Keywords: F22; F24; J61; I12; 330; emigration; alcoholism; Kyrgyzstan; Central Asia; monetary remittances; social remittances